HUBUNGAN ANTARA FAKTOR-FAKTOR PENDUKUNG DAN PENGHAMBAT EFEKTIVITAS KOMUNIKASI DENGAN TINGKAT EFEKTIVITAS KOMUNIKASI DALAM PROGRAM GERAKAN NASIONAL REHABILITASI HUTAN DAN LAHAN (GNR-HL) DI KECAMATAN KEDAWUNG KABUPATEN SRAGEN - Agung Wibowo; Suminah Suminah; Dwiningtyas Padmaningrum (Caraka Tani: Journal of Sustainable Agriculture, 2009)
The success of National Movement of Forest and Land Rehabilitation Program (GNR-HL) depends on active participation from any components, including government, program executives and also societies. Effective communication has an important role, because with communicatio, there will be established contacts and interaction among any supporting elements, including peasant-program participant, so that it can drive participant’s knowledge, behavior and skill transformation in an expected condition. The objectives of this research are (1) to analyze the communication effectiveness level in National Movement of Forest and Land Rehabilitation Program in District of Kedawung Regency of Sragen; (2) to analyze the supporting and interfering factors on community effectivenes regarding with communication effectiveness level in National Movement of Forest and Land Rehabilitation Program in District of Kedawung Regency of Sragen. Basic method used in this research is descriptive method. The location is determined in purposive (intended). In such case, the selected location is District of Kedawung Regency of Sragen, because this district has the highest average value in National Movement of Forest and Land Rehabilitation Program in District of Kedawung Regency of Sragen. Whereas to know the relation between the supporting and interfering factors in communication effectiveness with communication effectiveness level in National Movement of Forest and Land Rehabilitation Program, it is using Spearman’s Rank Correlation Formula. Socialization and elucidation activities in National Movement of Forest and Land Rehabilitation Program, in facts, are not provide new knowledge for the peasant-program participants. The use of the message is the most predominant factor and has highly significant relation with communication effectiveness level ini knowledge domain. The source credibility and closeness with the target are the related significant factors with communication effective level in knowledge domain. The source credibility factor is significant in 95% reliability level, whereas the closeness with the target significantly reach 99% reliability.